The intellectual: responsibility, betrayal and conflict - Calderón González, Jacinto H. (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
This article aims to show what it has meant to be an intellectual, emphasizing its original function in contrast to what is considered their betrayal. The article begins with the Dreyfus Affair and, with Benda and Chomsky, it will seek to qualify the task of the intellectual as well as his responsibility. The discussions offered here will lead us to observe the ideological dynamics of the 20th century and attention will be paid to the lifestyle of the intellectual, attending to the criticisms that Barthes collected about Poujade as well as the poisoned darts that Schopenhauer launched at the philosophers of his time. Darts that, according to post-truth, are quite current.